THEORIES OF EUROPEAN INTEGRATION: A META-THEORETICAL PERSPECTIVE - Oana – Andreea ION (Challenges of the Knowledge Society)
The aim of the article is to demonstrate that the theories of European integration are political theories. In this respect, I will refer to (a) what theory means, (b) what is the difference between theories from the Humanities disciplines and those from the Sciences areas, (c) what political theory stands for and (d) what is the relation between political theories and theories of European Integration, in the specific context of European Union Studies.